Dr. Martha Heasley Cox
This photo was taken on the occasion of the re-naming of the Steinbeck Center ceremony. In honor of Dr. Martha Heasley Cox, the name was changed from Steinbeck Research Center (SRC) to the Martha Heasley Cox Center for Steinbeck Studies. At this time the Center was located on the 3rd floor of the Wahlquist Library at San Jose State. This was the Steinbeck Center's 2nd location. From left: Ned Hearn (MHCCfSS Advisory Board member), Doctor Martha Heasley Cox, Jim Levitt (MHCCfSS Advisory Board member), Doctor Susan Shillinglaw (Director of MHCCfSS 1987-2005). Digital copy only. No hard copy.